Correction: Developments and recent advancements in the field of endogenous amino acid selective bond forming reactions for bioconjugation. (18th June 2015) - Koniev, Oleksandr; Wagner, Alain
Abstract : Correction for 'Developments and recent advancements in the field of endogenous amino acid selective bond forming reactions for bioconjugation' by Oleksandr Koniev et al., Chem. Soc. Rev., 2015, DOI: ; Web:10.1039/c5cs00048c .